ACTIVITY-BASED COSTING DAN SIMULATED ANNEALING UNTUK PENCARIAN RUTE PADA FLEXIBLE MANUFACTURING SYSTEMS - Budhi, Gregorius Satia (Institute of Research and Community Outreach - Petra Christian University, 2003)
Flexible Manufacturing System (FMS) is a manufacturing system that is formed from several Numerical Controlled Machines combine with material handling system, so that different jobs can be worked by different machines sequences. FMS combine the high productivity and flexibility of Transfer Line and Job Shop manufacturing system. In this reasearch, Activity-Based Costing(ABC) approach was used as the weight to search the operation route in the proper machine, so that the total production cost can be optimized. The search method that was used in this experiment is Simulated Annealling, a variant form Hill Climbing Search method. An ideal operation time to proses a part was used as the annealling schedule. From the empirical test, it could be proved that the use of ABC approach and Simulated Annealing to search the route (routing process) can optimize the Total Production Cost. In the other hand, the use of ideal operation time to process a part as annealing schedule can control the processing time well. Abstract in Bahasa Indonesia : Flexible Manufacturing System (FMS) adalah sistem manufaktur yang tersusun dari mesin-mesin Numerical Control (NC) yang dikombinasi dengan Sistem Penanganan Material, sehingga job-job berbeda dikerjakan oleh mesin-mesin dengan alur yang berlainan. FMS menggabungkan produktifitas dan fleksibilitas yang tinggi dari Sistem Manufaktur Transfer Line dan Job Shop. Pada riset ini pendekatan Activity-Based Costing (ABC) digunakan sebagai bobot / weight dalam pencarian rute operasi pada mesin yang tepat, untuk lebih mengoptimasi biaya produksi secara keseluruhan. Adapun metode Searching yang digunakan adalah Simulated Annealing yang merupakan varian dari metode searching Hill Climbing. Waktu operasi ideal untuk memproses sebuah part digunakan sebagai Annealing Schedulenya. Dari hasil pengujian empiris dapat dibuktikan bahwa penggunaan pendekatan ABC dan Simulated Annealing untuk proses pencarian rute (routing) dapat lebih mengoptimasi total biaya produksi. Sementara itu, dengan digunakannya waktu operasi ideal sebagai Annealing Schedule, waktu proses dapat dimaintain dengan baik. Kata kunci: Flexible Manufacturing Systems, Activity-Based Costing Approach, Simulated Annealing.